Examining the Effectiveness of Google Docs on Reducing Linguistic Challenges and Enhancing Narrative Essays Writing Quality The case of third year EFL bachelor students of Mohamed Cherif Messadia university of Souk Ahrass - ATMANI Hadjer (My University, 2024)
Abstract This study investigates the effectiveness of Google Docs in improving narrative essay writing for third-year English as a Foreign Language (EFL) bachelor students at Mohamed-Cherif Messaadia University. It addresses the persistent linguistic challenges students face, hypothesizing that Google Docs features can significantly reduce these issues and enhance essay quality. Using a quasi-experimental design and focus group interviews, the study examines the impact of Google Docs on grammar, vocabulary, spelling, and capitalization. Results show a notable decrease in linguistic challenges post-treatment, although the improvement in essay quality is not statistically significant. However, student perceptions towards Google Docs remain positive, supporting its value as a tool for writing improvement. This research provides valuable insights into the potential of digital tools in addressing writing challenges and suggests avenues for further exploration in educational practice. ------------------------ الملخص تهدف هذه الدراسة إلى استكشاف فعالية Google Docs في تحسين كتابة المقالات السردية لطلبة سنة ثالثة ليسانس بجامعة محمد الشريف مساعدية. تركز الدراسة على التحديات اللغوية المستمرة التي يواجهها الطلبة، وتفترض الدراسة أن ميزات Google Docs يمكن أن تقلل بشكل كبير من هذه التحديات وتعزز جودة المقالة. باستخدام تصميم شبه تجريبي ومقابلات مجموعات التركيز، تفحص الدراسة تأثير Google Docs على قواعد اللغة والمفردات والإملاء والتهجئة. تُظهر النتائج انخفاضًا ملحوظًا في التحديات اللغوية بعد المعالجة، على الرغم من أن التحسين في جودة المقالة لم يكن ملحوظًا إحصائيًا. ومع ذلك فإن تصورات الطلاب نحو Google Docs لا تزال ايجابية مما يدعم قيمتها كأداة لتحسين الكتابة. تقدم هذه الدراسة رؤى قيمة حول إمكانيات الأدوات الرقمية في مواجهة تحديات الكتابة وتقترح سبلًا لاستكشافها في الممارسة التعليمية. ------------------------- Résume Cette étude examine l'efficacité de Google Docs pour améliorer la rédaction de dissertations narratives pour les étudiants de troisième année de licence à l'Université Mohamed-Cherif Messaadia. Elle aborde les défis linguistiques persistants auxquels sont confrontés les étudiants, avec l'hypothèse que les fonctionnalités de Google Docs peuvent réduire considérablement ces problèmes et améliorer la qualité des dissertations. En utilisant une conception quasi-expérimentale et des discussions de groupe, l'étude examine l'impact de Google Docs sur la grammaire, le vocabulaire, l'orthographe et la mise en majuscule. Les résultats montrent une diminution notable des défis linguistiques après le traitement, bien que l'amélioration de la qualité de la dissertation ne soit pas statistiquement significative. Cependant, les perceptions des étudiants envers Google Docs restent positives, soutenant sa valeur en tant qu'outil d'amélioration de l'écriture. Cette recherche fournit des informations précieuses sur le potentiel des outils numériques pour relever les défis de l'écriture et suggère des pistes à explorer dans la pratique éducative